Role of Nitric Oxide in Plant Senescence - Hussain, Adil; Shah, Farooq; Ali, Farman; Yun, Byung-Wook (Frontiers in Plant Science, 2022)
In plants, senescence is the final stage of plant growth and development that ultimately leads to death. Plants experience age-related as well as stress-induced developmental ageing. Senescence involves significant changes at the transcriptional, post-translational and metabolomic levels. Furthermore, phytohormones also play a critical role in the programmed senescence of plants. Nitric oxide (NO) is a gaseous signalling molecule that regulates a plethora of physiological processes in plants. Its role in the control of ageing and senescence has just started to be elucidated. Here we review the role of NO in the regulation of programmed cell death, seed ageing, fruit ripening and senescence. We also discuss the role of NO in the modulation of phytohormones during senescence and the significance of NO-ROS cross-talk during programmed cell death and senescence.